Vertebral artery trauma: transcatheter embolization. - Ben-Menachem, Y; Fields, W S; Cadavid, G; Gomez, L S; Anderson, E C; Fisher, R G (American Journal of Neuroradiology, 1987)
Injuries of the vertebral arteries in four patients were treated by transcatheter embolization. Embolotherapy was performed after incomplete or unsuccessful surgery in three of the patients and as a preventive measure in lieu of surgery in the fourth patient. All procedures were successful and without complications. An injured vertebral artery is usually extremely difficult to approach surgically, but because of extensive collateral blood supply it is usually expendable; therefore, it becomes an inviting target for management by interventional angiographic techniques. Embolotherapy of an injured vertebral artery is easier, faster, and safer than its surgical ligation and, therefore, decidedly superior. With few exceptions, embolotherapy should be considered the preferred method in the management of vertebral artery trauma.